Comparisons of complex modulus provided by different DMA. (December 2018) - Henriques, I.R.; Borges, L.A.; Costa, M.F.; Soares, B.G.; Castello, D.A.
Abstract: Dynamic mechanical analysis (DMA) is one of the most common methods employed to study the materials' composition and properties. However, the complex modulus estimates provided by DMA are well-known to show divergences between samples and loading clamps. Few works in literature explore these divergences and do not address the mathematical formulation and comparative data of complex modulus in different operational modes provided by different DMA machines. Aiming at contributing to fill this gap, this work presents an investigation on the mathematical formulation for complex modulus determined by this technique and how it is evaluated in three operational modes by three different analyzers. Measurements were performed in single cantilever, dual cantilever and three-point bending modes using basically the same test conditions. Comparisons of the results were made in order to observe the effects of testing equipment and testing parameters. Highlights: The comparison among DMA's modulus provided by three different equipment is considered here. The correlation among different operational modes is investigated. The force and displacement time histories are analyzed. The mathematical formulation of each DMA is presented and discussed. The role of the modeling hypothesis is discussed concerning the DMA estimates.